Nature and Forms of Conflict in the Tea Industry of Assam with Special Reference to Dibrugarh District - Nath, Dayananda; Singha, Seema S (Journal of Commerce and Trade, 2015)
Conflict is an inevitable aspect in any organization. Conflict has an impact on individual, groups and organization. Often managers tend to devote a major portion of their productive time on conflict management. From an organizational perspective, conflicts may be simple and inevitable but their impact can be far reaching and critical that conflict management has to be given enough attention. The right amount of conflict will impact an organization in a positive fashion and will ensure to achieve its pre-oriented objectives. However, conflict which hamper organizational functioning that needs to be checked. Management’s perception to earn maximum profit and offer minimum benefit to their workers, whereas workers’ perception to achieve maximum benefit (both monetary and non-monetary) and offer minimum profit for their proprietor. These differences in perceptions are the root cause of conflict in tea gardens. The natures of conflicts in the tea gardens are both monetary as well as non-monetary. To get proper information questionnaire schedules are arranged considering the nature of conflict based on factors like: (i) management’s response on claims by workers to improve their existing housing condition (ii) satisfaction with the amount of compensation in case of industrial accident/occupational hazard, sickness (iii) problems with the changes of managerial personnel (iv) attitudes of workers with their present job and (v) class/role conflict among various categories of workers. After analysis of collected data actual problems have been sorted out and finally this paper concludes by offering suggestion to overcome these problems.